Atrial Natriuretic Peptide31–67: A Novel Therapeutic Factor for Cardiovascular Diseases - da Silva, Gustavo Jose Justo; Altara, Raffaele; Booz, George W.; Cataliotti, Alessandro (Frontiers in Physiology, 2021)
The characterization of the cardiac hormone atrial natriuretic peptide (ANP99-126), synthesized and secreted predominantly by atrial myocytes under stimulation by mechanical stretch, has established the heart as an endocrine organ with potent natriuretic, diuretic, and vasodilating actions. Three additional distinct polypeptides resulting from proteolytic cleavage of proANP have been identified in the circulation in humans. The mid-sequence proANP fragment 31-67 (also known as proANP31-67) has unique potent and prolonged diuretic and natriuretic properties. In this review, we report the main effects of this circulating hormone in different tissues and organs, and its mechanisms of actions. We further highlight recent evidence on the cardiorenal protective actions of chronic supplementation of synthetic proANP31-67 in preclinical models of cardiorenal disease. Finally, we evaluate the use of proANP31-67 as a new therapeutic strategy to repair end-organ damage secondary to hypertension, diabetes mellitus, renal diseases, obesity, heart failure, and other morbidities that can lead to impaired cardiac function and structure.